Administrative control of administrative protection work in Iraq - Aziz, Zainab; Merza, Waleed (Journal of Legal Sciences, 2022)
This research deals with the work of administrative protection (civil defense), which is vested in the authority of administrative control, and the latter directly related to public freedoms, as the maintenance of public order from various disasters and damage usually requires restriction In the area of ​​protection of population and property, the administration is forced to put restrictions on some public freedoms in particular, as the administrative protection aims to protect the security of citizens from the risks and the safety of their property, and the prevention of harmful residues that may arise from its exercise. (Civil Defense) Take a set of measures to reduce disasters and damage, working to organize work and controls are designed to protect the population and property. We dealt with the subject of administrative control of administrative protection work in Iraq in two topics, Vfredna the first topic of the definition of administrative protection and its subject, while the second section where we studied the definition of administrative control and its purposes and means of administrative protection. We have reached a number of conclusions and recommendations that we hope to be taken in the exercise of the administration of administrative control authorities to protect the population and property in lraq.